Indications and determinants of caesarean section in Al Batool teaching hospital - Ahmed Zidan , Fatin; Ghazal Noaman , Nadhim; Salih Mahdi , Ahmed; Kassem Saleh , Mohammad (Diyala Journal of Medicine, 2024)
Background: C-section (caesarean section) is a lifesaving procedure when certain complications arise during pregnancy and labor. however, it’s a major surgery and associated with immediate maternal and perinatal risks and may have implications for future pregnancies as well as long term effects. Objective: To describe indications and determinants of caesarean section in Al Batool teaching hospital in Diyala during the study period. Patients and Methods: Across sectional study conducted among women admitted to Al Batool teaching hospital and delivered by C-section from first of October 2022 to 15th of march 2023. Results: A total of 150 women underwent C-section enrolled in this study during the study period, age of participants ranged from 19-35. out of them, 88(59%) sections were elective and 62(41%) sections were emergent. commonest indication for emergency C-section was fetal distress (62%) and commonest indication for elective C-section was previous cesarean (33%). Conclusion: Parity, residence, education, and antenatal care visits were significant determinants for C-section. previous C-section, maternal request and malpresentation were commonest indications for such procedure.